The Existence of the Jepin Langkah Loncat Tiung Sembilan Dance in Pontianak - Ricki, Ricki; Oktariani, Dwi; Ismunandar, Ismunandar (Universitas Tanjungpura, 2024)
The development of dance continues to advance in line with people's lives. Traditional dances generally experience developments that are influenced by the surrounding community, whether the community is a supporting or inhibiting factor for the dance. One of the traditional dance arts that has developed to date is the Jepin Langkah Loncat Tiung Sembilan dance which is currently developing in Pontianak and its surroundings. The Jepin Langkah Loncat Tiung Sembilan dance is a Jepin Langkah dance that was originally developed in 1932 by an artist named Salim Kudong in Kalimas Village, Sungai Kakap District, Kubu Raya Regency. In 1947 Salim Kudong taught Jepin Langkah to Mr Yusuf Daiman. Mr. Yusuf Daiman passed it on to the next generation, namely Mr. Sabaruddin, in 1967. Mr. Sabaruddin developed the Jepin Langkah by taking 9 Jepin Langkah that is langkah bujur (pelebat), langkah gersik, langkah sorong dayung, langkah jarum mesin, langkah betiti batang, langkah baki juadah, langkah tak sampai, langkah loncat tiung, dan langkah besikut so that they become one dance known as the Jepin Langkah Loncat Tiung Sembilan dance. This research aims to describe the existence of the Jepin Langkah Loncat Tiung Sembilan dance. This research uses a qualitative method with an ethnochoreological approach. The existence of the Jepin Langkah Loncat Tiung Sembilan dance cannot be separated from the community, researchers, and government who are supporting factors. Meanwhile, inhibiting factors such as people's interest in studying dance traditions still need greater attention.